2019
DOI: 10.1021/acs.iecr.9b03577
|View full text |Cite
|
Sign up to set email alerts
|

Building a Microkinetic Model from First Principles for Higher Amine Synthesis on Pd Catalyst

Abstract: The hydrogenation of nitriles utilizing heterogeneous catalysis is a significant commercial process for the synthesis of primary, secondary, and tertiary amines. Periodic plane-wave density functional theory (DFT) is used to examine the hydrogenation of acetonitrile to primary, secondary, and tertiary amines on palladium catalysts. The quantified minimum energy reaction pathways, including activation barriers, for acetonitrile reaction to higher amines are discussed. The construction of a microkinetic model fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Adamczyk et al very recently reported detailed calculations of hydrogenation of acetonitrile on Pd and Co catalysts 6971 . However, to our knowledge, theoretical calculations of hydrogenation of BN on metals have not been reported yet.…”
Section: Resultsmentioning
confidence: 99%
“…Adamczyk et al very recently reported detailed calculations of hydrogenation of acetonitrile on Pd and Co catalysts 6971 . However, to our knowledge, theoretical calculations of hydrogenation of BN on metals have not been reported yet.…”
Section: Resultsmentioning
confidence: 99%
“…The positions of the desorption peaks of the desorption curves were correlated with the strength of action of the metal hydrogenation active sites. Ni/CN had desorption peaks at 265 and 442 °C and Al 2 O 3 /CN had desorption peaks at 228 and 435 °C, whereas the two desorption peaks of 3Ni–Al 2 O 3 /CN at higher temperatures of 400 and 510 °C belonged to the strong bonding of adsorbed H 2 to the Ni substrate as well as the hydrogen spillover onto Al 2 O 3 . And the desorption peaks are all shifted to higher temperatures, indicating that the hydrogen overflow on the surface of 3Ni–Al 2 O 3 /CN with introduced Al is more easily utilized.…”
Section: Resultsmentioning
confidence: 96%
“…The theoretical study has been performed utilizing periodic plane-wave DFT calculations as implemented in the Cambridge Serial Total Energy Packages (CASTEP). The spin polarized generalized gradient approximation with Perdew–Burke–Ernzerhof functional has been used with Kohn–Sham orbitals with an energy cutoff of 400 eV. , The effect of the core electrons has been expressed with the Vanderbilt Ultrasoft Pseudopotentials (USPP) method . To provide hydrogen chemisorption energies and geometries for the MoCh 2 /Gr nanocomposite in line with experimental observations, an improved description of the nonlocal nature of the electron correlation, in particular van der Waals interactions, was accounted for using a semi-empirical dispersion energy correction by the method of Tkatchenko and Scheffler .…”
Section: Methodsmentioning
confidence: 99%